Septembrsko neurje v zgornji Selški dolini - Debeljak, Nika (Geografski obzornik, 1997)
The damages done by the weather yearly represent a considerable burden on the national income and consequently an expensive impediment to the development of both the region and the country. In this treatise the causes as well as the consequences of the floods which damaged the upper parts of the Selska valley on September 8 and 9, 1995 are presented.
Keywords: 1995; Gorenjska; naravne nesreče; neurja; poplave; Selška dolina; usadi; zemeljski plazovi